Ionic liquid pretreatment as emerging approaches for enhanced enzymatic hydrolysis of lignocellulosic biomass - Elgharbawy, Amal A.M.; Alam, Md Zahangir; Moniruzzaman, Muhammad; Goto, Masahiro (Elsevier, 2016)
Ionic liquids (ILs) have been increasingly exploited as solvents and/or reagents in many applications due to their “green” properties as well as their tunable physicochemical and biological properties. One of them is the pretreatment of lignocellulosic biomass prior to enzymatic hydrolysis for bioenergy and biomaterials production. Generally, the process composed of an IL pretreatment/recovered followed by enzymatic hydrolysis of lignocellulosic biomass. Another approach was developed in which simultaneous pretreatment and saccharification of biomass in ILs were performed. However, the use of ILs in this integrated process, in which enzymatic hydrolysis is done in the presence of IL applied for biomass pretreatment, can easily inactivate the enzymes. Cellulases, one of the most important hydrolytic enzymes used to catalyze the polysaccharide, showed good levels of stability in many ILs. In addition, various approaches were made including synthesis of enzyme-compatible ILs, screening ILs-tolerant enzymes and media engineering to improve cellulases performance. In this review paper, recent advances of the hydrolysis of lignocellulosic biomass in a single-step process in ILs will be highlighted. Various cellulase stabilization approaches and the design of enzyme compatible biomass-dissolving ILs are also discussed. We strongly believe that IL-compatible cellulase systems would eliminate the need to recover the regenerated biomass and lead to a simple, in situ saccharification of cellulosic materials, which would be beneficial in developing integrated bioprocesses.